Application of Smart Relay Software in 3-Phase Motor Practice at SMKN 2 Bitung - Alsius Lagu; I Gede Wardana (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to detect practical errors to minimize circuit errors. This research was carried out at SMK Negeri 2 Bitung in the even semester of the 2021/2022 academic year. The research method used is descriptive analysis research using quantitative and qualitative approaches. The data collection technique consists of three stages: observation, statements based on Bloom's taxonomy, and documentation. The subjects of this research were 25 students from class XII. The research instrument used is a statement based on Bloom's taxonomy which has gone through the validation stage of the supervisor. The results of this study are to minimize the occurrence of 3-Phase Motor Practice errors with the application of Smart Relay software for 25 students. The results showed they dominated with friendly answers regarding students' understanding of using Smart Relay software. Based on students' attitudes in using Smart Relay software, they dominate with agreeing answers, and so on, aspects of students' skills in using Smart Relay software dominate with agreeing answers. It was also obtained from student learning outcomes that understanding the Smart Relay software got an average score of 84.2.